Preparation and Deposition of Oxides of Some Metals and Ferrite on Aluminum and Study of the Absorption In a range Electromagnetic Frequencies - Taha Hussein Lazem,; Hasanein Nouri Hamza, (Eximia, 2025)
Two-layer coatings were prepared, one layer of different metal oxides (TiO2,Fe2O3, ZnO, MgO, CuO, CdO, Ni2O3, MnO2) and the other of ferrite powder (MnFe2O4) on aluminum for each sample. The absorbance of electromagnetic waves in the frequency range (8-12.5) GHz was measured using a standing wave ratio )SWR( and the effect of exchanging the oxide layer with the ferrite powder layer upon direct exposure to ultraviolet radiation was studied. It was observed that the oxide layer (MnO2) and the oxide layer (Ni2O3) were the best among the prepared samples due to their high absorbance values close to the ferrite layer when exposed to ultraviolet radiation directly and in exchange with the ferrite layer. MnO2 oxide with ferrite gave an absorbance of (87%) in the frequency range (10.2-11.4) GHz, while (Ni2O3) oxide with ferrite gave an absorbance of (80.5%) in the frequency range (10.8-12.4) GHz, compared to the other prepared samples.